Effects of Entrepreneurial and Environmental Sustainability Orientations on Firm Performance: A Study of Small Businesses in the Philippines. (1st December 2017) - Roxas, Banjo; Ashill, Nicholas; Chadee, Doren
Abstract : Why do small businesses in developing countries embrace sustainable business practices and what are the effects on their performance? We address these questions by drawing on the natural‐resource based view of the firm to argue that the environmental sustainability orientation of small businesses can be explained by their entrepreneurial orientation. Our study of 197 small businesses in the Philippines shows that an entrepreneurial strategic orientation enables them to develop a more proactive stance toward environmental sustainability practices which lead to superior firm performance. The implications of the findings for future research and for public policy for small businesses are also discussed.